Applying Humanistic Principles in Arabic Language Learning: A Literature Review on Developing Motivation and Learner Autonomy - Muhammad Lutfi Asfihani; Hayyi Alawiyah Munidzar (Universitas Islam Tribakti Lirboyo, Kediri, 2025)
This study examines the application of humanistic principles in Arabic language learning, emphasizing their role in developing students' motivation and learning independence. The research employs a library research method by systematically reviewing primary and secondary sources including journal articles, research findings, and academic works published between 2015 and 2025 that are relevant to humanistic education, Arabic language pedagogy, motivation, and learner autonomy. Data were collected through documentation techniques and analyzed using content analysis and qualitative descriptive analysis. The analytical stages consisted of: (1) collecting and selecting relevant literature, (2) reducing data by identifying major themes, (3) classifying concepts based on the humanistic theories of Carl Rogers, Abraham Maslow, and Gestalt psychology, and (4) drawing inductive conclusions from recurring patterns and findings. The results indicate that the application of humanistic principles positively influences students’ motivation and learning independence. The research gap identified in this study lies in the limited number of investigations directly connecting humanistic pedagogy with the development of learning independence in Arabic language education. Most previous studies focus on school-level learners rather than university students, and longitudinal research remains scarce. Overall, this study concludes that the application of humanistic principles strengthens intrinsic motivation and fosters learner independence. Future research is recommended to adopt empirical and longitudinal approaches to explore the long-term effects of humanistic education and to develop specific instruments for measuring learning independence in Arabic language contexts.